High-school seniors' college enrollment goals: Costs and benefits of ambitious expectations. (December 2015) - Villarreal, Brandilynn J.; Heckhausen, Jutta; Lessard, Jared; Greenberger, Ellen; Chen, Chuansheng
Abstract: High school students with high long-term educational expectations attain higher levels of education than those with lower expectations. Less studied is the role of students' short-term college enrollment expectations for the year after high school graduation. The purpose of the current study was to examine the costs and benefits of ambitious short-term expectations and the impact of falling short of these expectations on mental health, motivation, and educational outcomes. Over 1000 youth with expectations to attend college were surveyed during their senior year of high school, one year later, and four years later. Participants who did not achieve their short-term expectations had lower educational attainment four years later but were not less satisfied with their educational progress. The negative consequences of falling short of one's expectations were restricted to individuals with less ambitious short-term expectations. Thus, the benefits of ambitious short-term expectations for youth may outweigh the costs.